Finding Turtle Farm : My Twenty-Acre Adventure in Community-Supported Agriculture - Tedesco, Angela, 1948- (Book collections on Project MUSE., 2022)
"On a twenty-acre farm in Iowa in 1995, Angela Tedesco planted the seeds of Turtle Farm, introducing Community Supported Agriculture to Iowa. In Finding Turtle Farm, Tedesco recounts this adventure in all its down-and-dirty work and wonder, from plan and plot to harvest, in an ultimately hopeful account of what it means to meet the most basic of human needs"--